Clinical response to antibiotic regimens in lower limb cellulitis: a systematic review. (1st January 2021) - Mistry, K.; Sharma, S.; Patel, M.; Grindlay, D.; Janjuha, R.; Smart, P.; Levell, N. J.
Summary: There is variation in the treatment of lower limb cellulitis (LLC) with no agreement on the most effective antibiotic regimen. Many patients with cellulitis fail to respond to first‐line antibiotics. This can negatively affect patient care and result in unnecessary hospital admissions. The aim of this systematic review was to determine the clinical response and safety of antibiotic regimens for the management of LLC. A systematic review for randomized controlled trials (RCTs) was conducted using OVID MEDLINE, Ovid Embase and Cochrane Central Register of Controlled Trials in January 2019. Outcomes of interest included the clinical response to antibiotic regimens (type, dose, route, duration) and the safety of antibiotics in LLC. Trial quality was identified using the Cochrane Risk of Bias tool. Four RCTs were included. All included studies showed no significant differences between the clinical response to different antibiotic type, administration route, treatment duration or dose. LLC may be overtreated and shorter courses of oral antibiotics, possibly with lower doses, may be more suitable. There is a lack of published data on the clinical response and safety of antibiotics in LLC. Three studies were high risk for bias overall. Further high‐quality studies may help determine whether less intensive antibiotic regimens can effectively treat LLC. Abstract: Click here for the corresponding questions to this CME article.